Effect of different-condition parameters on frictional properties of non-asbestos phenolic resin-based friction material. (May 2017) - Luo, Ying; Yang, Zhaojian
In allusion to WSM-3 non-asbestos phenolic resin-based friction material, the experimental devices are set up for studying tribological properties of the WSM-3 resin-based non-asbestos brake shoe braking on 16Mn steel. According to collected experiential data of physical test, the change rules of the transient/mean friction coefficient are studied with contact pressure, sliding velocity, and contact surface temperature, and then the curves are drawn. The changing law of the friction coefficient is explored with the different-condition parameters, and the variation mechanism of friction performance of WSM-3 brake shoe material is discussed. The experiment results show that the frictional properties of the materials have not only strong system dependency but also strong coupling with the working conditions of the system. It is required to consider the transient friction coefficient or the average coefficient of friction as a variable in the material tribological design.